2010
DOI: 10.1159/000319468
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Response Kinetics from Cultured Mouse Olfactory Epithelium at Different Ages in vitro

Abstract: Mammalian olfactory epithelium can withstand the external environment, undergo life-long regeneration, and respond to thousands of odorant stimuli, making it an attractive system for a variety of studies. Previously, we described a long-lived olfactory coculture of olfactory epithelium and bulb tissues and we present here the kinetic properties of that culture system. Neonatal mouse epithelial-bulbar explants were grown for periods as long as 121 days in vitro (DIV), nearly doubling the survival time of our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…Both developmental stages also express >1,100 genes encoding proteins that bind zinc or are predicted to bind zinc. Although the unusual sensitivity of OSNs to zinc might lie within the functions of these gene products (Lim et al, 2009; Viswaprakash et al, 2010) it is very possible that elevated zinc in the olfactory epithelium affects proteins that do not normally bind zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Both developmental stages also express >1,100 genes encoding proteins that bind zinc or are predicted to bind zinc. Although the unusual sensitivity of OSNs to zinc might lie within the functions of these gene products (Lim et al, 2009; Viswaprakash et al, 2010) it is very possible that elevated zinc in the olfactory epithelium affects proteins that do not normally bind zinc.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that zinc nanoparticles enhanced EOG responses of cultured olfactory neurons. The fact that zinc nanoparticle enhancement was observed in both young and mature cultures as well as in dissected olfactory epithelium indicates the importance of this phenomenon for initial events in olfaction (Viswaprakash et al 2009b).…”
Section: Discussionmentioning
confidence: 87%
“…Based on previous in vitro ( 18 , 20 , 36 ) and in vivo ( 21 ) studies, we concluded that olfactory enhancement by the zinc nanoparticles is composed of two components. One component is based at the level of olfactory sensory receptors, and the second part of the olfactory enhancement is positioned at higher levels of olfactory perception.…”
Section: Introductionmentioning
confidence: 74%